PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN KEPEMILIKAN MANAJERIAL TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS DAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013--2015 - Humairoh, Fitri (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2018)
The purpose of this study was to examine the influence of Corporate Social Responsibility and Managerial Ownership on Firm’s Value, analysis profitability as moderating variable in the relationship between Corporate Social Responsibility with firm's value and Managerial Ownership with Firm's Value. And also to examine Firm Size as a moderating variable in the relationship between Corporate Social Responsibility with firm's value and Managerial Ownership with Firm’s Value. Data for this research were obtained from the firm's annual report and financial statement on the Indonesia Stock Exchange (IDX) site. A sample used in this research are 120 manufacturing companies that listed on the Indonesia Stock Exchange from 2013-2015. The sampling technique used is purposive sampling method. This research uses a regression analysis. Based on the analysis it can be concluded that the significant positive effect of Corporate Social Responsibility on firm’s value. Managerial Ownership has no effect on a firm's value. Profitability can be a moderating variable between Corporate Social Responsibilities with Firm's Value, but cannot be a moderate variable between Managerial Ownership with Firm’s Value. Firm Size cannot be a moderating variable between Corporate Social Responsibilities with Firm's Value and cannot be a moderating variable between Managerial Ownership with Firm's Value.